Associations Between Physical Activity, Sedentary Behaviour, Sleep Quality, and Anxiety Among Healthy Pain-Free Adults in Saudi Arabia: An Online Cross-Sectional Survey - Mansour Abdullah Alshehri; Areej Ali Alzylai; Joree Abdulrahman Alshehri; Lana Zaid Alsharif; Wafa Saleem Almalki; Hammad S. Alhasan; Ammar S. Fadil; Moayad Saleh Subahi; Hosam Alzahrani (Sports, 2025)
Physical activity, sedentary behaviour, sleep quality, and anxiety are interrelated factors that play a critical role in physical and mental health. However, limited evidence exists on their associations within the Saudi Arabian context. This study aimed to investigate the relationships between physical activity, sedentary behaviour, sleep quality, and anxiety symptoms among healthy, pain-free adults in Saudi Arabia. A cross-sectional online survey was conducted between December 2024 and April 2025 using validated Arabic versions of the Global Physical Activity Questionnaire (GPAQ), the Brief Pittsburgh Sleep Quality Index (B-PSQI), and the Generalised Anxiety Disorder-7 (GAD-7). The data were analysed using descriptive statistics and multivariable linear regression models. A total of 185 participants (mean age = 33.99 ± 12.57 years; 69.73% female) were included. The average total physical activity was 1730.02 ± 2109.24 MET min/week, and the mean sedentary time was 6.77 ± 4.69 h/day. No significant associations were found between physical activity and either sleep quality or anxiety symptoms. Similarly, sedentary behaviour time was not significantly associated with sleep quality or anxiety symptoms. However, poorer sleep quality was significantly associated with higher anxiety levels. These findings highlight the importance of sleep quality in mental health strategies for healthy adults in Saudi Arabia.